STEAM TRAINING BASED ON BULLANGIC CLASS PERPETUATION OF COMPETENTLIGINING TECHNOLOGY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The abbreviation STEM is an abbreviation of the words science, technology, engineering, mathematics. It stands for "education based on science, technology, engineering and mathematics." This approach to education integrates engineering knowledge, natural sciences, the development of "flexible" skills and is aimed at practical activities. And not so long ago, a new STEAM term appeared, which also includes the Arts category.This term was first proposed in 2001, and in recent years has received special development. And if the method was originally aimed at university education, today it has become clear that it works perfectly with children of school and preschool age.